Prosedur Penggajian Pegawai Di Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Daerah Pemerintah Kabupaten Sumba Tengah - Ansgarius Umbu Kabalu; Zaenal wafa (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
Compensation for employees of the Regional Personnel Agency and HR Development in Central Sumba Regency is the subject of this research. This research was designed as a qualitative descriptive study. Interviews, observations, and documentation are ways of collecting data; data reduction, draw data visualization, and analysis of stud results. The results showed that the researcher found a problem when inputting employee data by the salary treasurer, this was because the data provided was still done manually and a large number of employee data worked on by one employee is also one of the problems in the input process, because it is more prone to occur errors. based on the findings of a month-long research at the Office of the Staffing and Human Resources Development Agency in Central Sumba Regency. Practitioners came to the conclusion that as long as the payroll system was running quite well at the Office of the Central Sumba Regency Personnel and Human Resources Development Agency, there was still room for improvement and additions to ensure all components existed and functioned. properly to improve internal control.